Use of GIS to predict potential erosion areas in a typical Mediterranean watershed - Belaid H.; Karteris M.A. (Agriculture, durabilité et environnement, 1995)
Erosion can be considered as a major environmental problem in the Mediterranean area, in particular in Tunisia, Greece, Italy and Spain. In this study, Geographic Inforation Systems (GIS) (GRASS) were used to establish an information data base to characterize a watershed in northern Greece, and locate potential erosion areas using proximity analysis and modelling involving six layers. GIS characterized the watershed easily and efficiently. The possibility of using GRASS to generate buffer zones around linear and area features helped to quantify sensitive areas close to streams. Better results were obtained using a complex model based on weight assignment and using geology, soil, rainfall, slope, first order stream buffer zones and land cover/use. The model located potential erosion areas which need control and preventive measures according to the degree of erosion. The problem of cell resolution was overcome by reference to the mapping scale and other factors.
Séminaire de l'Association Tunisienne des Anciens de l'Institut Agronomique Méditerranéen de Zaragoza (ATA-IAMZ), 1993/12/02-03, Tunis (Tunisia)